Integrating User Acceptance Evaluation into District-Level Mobile Health System Design for Maternal Care - Arif Setia Sandi Ariyanto; Purwono Purwono; Deny Nugroho Triwibowo (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2026)
Many mobile health information systems are developed based primarily on technical requirements, while user acceptance is often assessed only after deployment and rarely integrated into the design process. This study addresses that gap by incorporating user acceptance evaluation as a design-informed feedback mechanism in the development of a district-level mobile health information system for maternal care. An applied research approach was used through system development, pilot deployment across five sub-districts, and post-use evaluation involving 74 active users. User acceptance was assessed using structured questionnaires covering perceived usefulness, perceived ease of use, consultation feature acceptance, and automated conversational support acceptance. The results showed high overall acceptance, with direct consultation with local midwives receiving the highest score (mean = 4.41; SD = 0.52), followed by consultation routing effectiveness (mean = 4.35; SD = 0.55). Perceived ease of use was positively associated with consultation feature acceptance (ρ = 0.46, p < 0.01). Automated conversational support was positively perceived but obtained lower scores (mean = 3.92) than human-based consultation features, indicating its complementary role. These findings demonstrate that user acceptance evaluation can provide actionable evidence for iterative system refinement and support the development of context-aware mobile health systems for maternal care.